Level of acceptance and nutritional value of milkfish (Chanos chanos) and mocaf flour food bars as local food-based emergency food alternatives - Maulana Ardhan, Muhammad; Aprilia, Veriani; Zuhrotun Nisa, Fatma; bin Ibrahim, Muhammad (Jurnal Gizi dan Dietetik Indonesia (Indonesian Journal of Nutrition and Dietetics), 2026)
ABSTRAKLatar Belakang: Indonesia sering mengalami bencana alam yang menyebabkan korban mengalami keterbatasan makanan dan asupan makan berkurang. Pangan darurat kaya protein dan karbohidrat, dari bahan lokal dapat dikembangkan. Tujuan: Mengembangkan produk alternatif pangan darurat berbasis pangan lokal berbentuk food bar dari ikan bandeng dan tepung mocaf dan tinjauannya dari tingkat kesukaan dan nilai gizi.Metode: Penelitian ini berjenis eksperimental dengan rancangan acak lengkap. Sampel yaitu food bar berbahan dasar ikan bandeng dan tepung mocaf dengan rasio konsentrasi 1:1 (F1), 3:2 (F2), dan 2:3 (F3). Sampel diuji tingkat kesukaannya menggunakan 30 panelis semi terlatih. Tingkat kesukaan terbaik ditentukan dari analisis statistik Kruskal-Wallis dan Mann-Whitney untuk warna, aroma, rasa, dan tekstur. Perlakuan terbaik diuji nilai gizi makro dengan analisis proksimat. Data kemudian dianalisis dengan uji independent sample t-test untuk mengetahui perbedaan nilai gizi pada kelompok kontrol dan kelompok perlakuan.Hasil: Perbedaan formula food bar memengaruhi secara signifikan tingkat kesukaan rasa, tekstur, dan warna (p<0,05), namun tidak memengaruhi aroma (p>0,05). Tingkat kesukaan terbaik dipilih F3 karena memiliki nilai skor kesukaan tertinggi dibanding formula lainnya. Nilai gizi abu (mineral), air, lemak, protein, dan kalori pada formula F3 lebih tinggi signifikan dibanding dengan F0 (kontrol), sementara kadar karbohidrat lebih rendah dibanding F0.Kesimpulan: Ada pengaruh variasi rasio konsentrasi ikan bandeng dan tepung mocaf terhadap tingkat kesukaan rasa, tekstur, dan warna. Perlakuan juga meningkatkan nilai gizi abu (mineral), air, lemak, protein, dan kalori. Food bar ini dapat dikembangkan menjadi pangan darurat lokal.   ABSTRACTBackground: Indonesia often experiences natural disasters that cause victims to suffer from food shortages and reduced food intake. Emergency food supplies rich in protein and carbohydrates can be developed from local ingredients.Objectives: Developing alternative emergency food products based on local foods in the form of food bars made from milkfish and mocaf flour, and evaluating their level of acceptability and nutritional value.Methods: This study was experimental in nature with a completely randomized design. The samples were fish-based food bars made from milkfish and mocaf flour with concentration ratios of 1:1 (F1), 3:2 (F2), and 2:3 (F3). The samples were tested for palatability using 30 semi-trained panelists. The best level of preference was determined from the Kruskal-Wallis and Mann-Whitney statistical analyses for color, aroma, taste, and texture. The best treatment was tested for macro nutritional value using proximate analysis. The data were then analyzed using an independent sample t-test to determine the difference in nutritional value between the control group and the treatment group.Results: Differences in food bar formulas significantly affect taste, texture, and color preferences (p<0.05), but do not affect aroma (p>0.05). The best preference level was selected for F3 because it had the highest preference score compared to other formulas. The nutritional values of ash (minerals), water, fat, protein, and calories in formula F3 were significantly higher than in F0 (control), while the carbohydrate content was lower than in F0.Conclusions: There is an effect of the variation in the ratio of milkfish concentration and mocaf flour on the level of preference for taste, texture, and color. The treatment also increases the nutritional value of ash (minerals), water, fat, protein, and calories. This food bar can be developed into local emergency food.